Henry the Fourth, part one - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works. 2003., 2006)
While England is threatened by the Earl of Northumberland, Young Prince Hal cavorts in London's taverns, accompanied by the dissolute, entertaining Falstaff and his band of rogues. Much of this play's tension involves Prince Hal and Falstaff, as the former tries to live up to his duties and responsibilities. In creating Falstaff Shakespeare gave us one of the theater's most enduring and memorable characters.